Access to Breathing Medications in an Uninsured and Underinsured Patient Population - Amanda M Singrey; Maria C. Pruchnicki; Jennifer Seifert; Juan Peng; Gregory Young; Kristin A. Casper (University of Minnesota Libraries Publishing, 2016)
The purpose of this study was to explore access to breathing medications in an uninsured and underinsured patient population and identify needs for additional medication access resources. Quantitative data were collected from a dispensing report, financial database, and medical records review of patients who filled prescription medications at a charitable pharmacy in Ohio between December 11, 2014 and March 11, 2015, and qualitative data were collected from five semi-structured interviews with patients regarding breathing medication access. A total of 181 patients filled a breathing medication during the study period, which is nearly a quarter of the pharmacy's patient population. The majority of patients were African American or Caucasian, and almost half were uninsured. Ultimately, the pharmacy had to purchase nearly half of breathing medications provided despite utilizing several medication access routes. Thus, access remains a significant challenge. Efforts are needed to ensure that vulnerable populations can consistently access breathing medications.   Type: Clinical Experience